Synthesis of protected 3-aminopiperidine and 3-aminoazepane derivatives using enzyme cascades. Issue 57 (12th June 2020) - Ford, Grayson J.; Kress, Nico; Mattey, Ashley P.; Hepworth, Lorna J.; Baldwin, Christopher R.; Marshall, James R.; Seibt, Lisa S.; Huang, Min; Birmingham, William R.; Turner, Nicholas J.; Flitsch, Sabine L.
Abstract : Synthesis of Cbz-protected 3-aminopiperidine and 3-aminoazepane using a multi-enzyme cascade consisting of galactose oxidase and imine reductase variants. Abstract : Multi-enzyme cascades utilising variants of galactose oxidase and imine reductase led to the successful conversion of N -Cbz-protected l -ornithinol and l -lysinol to l -3- N -Cbz-aminopiperidine and l -3- N -Cbz-aminoazepane respectively, in up to 54% isolated yield. Streamlining the reactions into one-pot prevented potential racemisation of key labile intermediates and led to products with high enantiopurity.